A comparison between pineapple hybrids with the Perola cultivar - Gadêlha, Ricardo Sérgio Sarmento (Pesquisa Agropecuaria Brasileira, 2014)
A comparison among the pineapple hybrids 3607, 1190 and 910 with the Perola cultivar was made. The hybrid 3607 showed a high significant difference, at the 1% level in relation to the other hybrids and the cultivar Perola, with the following average values for the characters investigated: 1156 g for fruit weight, 11.8 cm fruit diameter; 77.9 g crown weight; 2.4 cm pith diameter; 1.14 total acidity and 34.44 leaves per plant. The Perola cultivar was significantly different at the 1% level in the fruit mean length (15.6 cm), total soluble solids (13.57° Brix), and mean plant height (74.4 cm). The hybrid 3607, flowered first, about 520 days after planting and the hybrid 1190 was the last to flower.
Keywords: pineapple; genetics; hybrids; Pérola cultivar; comparison